2012
DOI: 10.1149/2.072208jes
|View full text |Cite
|
Sign up to set email alerts
|

3D Structure of Electrode with Inorganic Solid Electrolyte

Abstract: A 3D structure of electrode with inorganic solid electrolyte was prepared by sol-gel process. Li 0.35 La 0.55 TiO 3 (LLTO) precursor sol was injected into the pore networks of the sintered LiCoO 2 (LCO) with 72% relative density. After gelation and following heat treatments, composite material composed of sintered LCO and amorphous LLTO was obtained. The composite electrode had up to 93% relative density. The electrodes delivered 84% of the theoretical capacity at C/20 discharge rate. And 46% of the theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In this work the resultant amorphous film was annealed at 600 • C, a relative low temperature, and the XRD result showed that the thin film remained amorphous, consistent with our previous study. 26 Ionic conductivity of amorphous LLTO thin films.-Ionic conductivity was assessed by employing electrochemical impedance spectroscopy on amorphous LLTO thin films with a thickness of ∼0.30 μm (see Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work the resultant amorphous film was annealed at 600 • C, a relative low temperature, and the XRD result showed that the thin film remained amorphous, consistent with our previous study. 26 Ionic conductivity of amorphous LLTO thin films.-Ionic conductivity was assessed by employing electrochemical impedance spectroscopy on amorphous LLTO thin films with a thickness of ∼0.30 μm (see Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…22,23 In contrast with crystalline LLTO, amorphous LLTO z E-mail: yanwang@wpi.edu does not display the instability of its crystalline counterpart while still maintaining high lithium ion conductivity. [24][25][26] Li metal can be used as anode. 27 Among all possible anode materials, Li metal is the most attractive because of its favorable thermodynamic electrode potential and high specific capacity.…”
mentioning
confidence: 99%
“…The preparation is described in detail elsewhere. 22 These as-prepared powders were analyzed with X-ray Diffraction. In order to obtain amorphous LLTO, the annealing temperature was 600 • C. For crystalline one, the temperature was 1100 • C.…”
Section: Methodsmentioning
confidence: 99%
“…The formation of solid lithium electrolyte and electrode material composite was sometimes used in solid-state LIBs to improve the performance by reducing the charge-transfer polarization resistance. Previously, we proposed a new concept for improving the rate capability and cycling stability of Li 4 Ti 5 O 12 anode by forming micrometer-sized solid lithium electrolyte–Li 4 Ti 5 O 12 nanocomposite . The in situ formed Li 3 x La 2/3– x TiO 3 (LLTO) solid lithium electrolyte could improve the apparent lithium conductivity of the electrode material, thus effectively reducing the polarization resistance at fast rate, consequently improving the rate performance, while the formation of the composite could reduce the contact surface area between the Li 4 Ti 5 O 12 electrode and liquid electrolyte, thus improving the cycling stability.…”
Section: Introductionmentioning
confidence: 99%